How should fetal surgery for congenital diaphragmatic hernia be implemented in the post‐TOTAL trial era: A discussion. (22nd January 2022) - Deprest, Jan; Flake, Alan
Abstract: Following prenatal diagnosis of congenital diaphragmatic hernia, severity can be predicted based on the presence of associated abnormalities, and in isolated cases, on lung size and position of the liver. Severe hypoplasia is defined by a contralateral lung size <25% on ultrasound; moderate hypoplasia is when that lung measures between 25% and 45% of the normal. In fetuses with predicted poor postnatal outcome a procedure that reverses pulmonary hypoplasia may be considered. In uncontrolled studies, fetoscopic endoluminal tracheal occlusion (FETO) improved neonatal outcome. Recently, two randomized controlled trials compared the neonatal and infant outcomes in fetuses with isolated CDH (www.totaltrial.eu ). In severe cases, FETO was carried out at 27 +0 –29 +6 weeks' gestation (referred to as "early") and in moderate at 30 +0 –31 +6 weeks ("late"). Survival to discharge from the neonatal intensive care unit increased by 25% (95%‐CI:+6 to +46; p = 0.0091) and 13% (−1 to +28; p = 0.059), in fetuses with severe and moderate cases, respectively. Following FETO gestational age at delivery was on average 3.2 (2.3–4.1) weeks earlier following early and 1.7 (1.1–2.3) following late FETO. Here the strengths and weaknesses of the TOTAL trials and their translation to the clinic are debated. Discussants are the lead for the trial (JD) and a colleague (AF) not involved. The discussant notes that the observed survival, both in treated and expectantly managed fetuses, was overall less than what is reported by some high volume centers, particularly in North America. Additional criticisms are the potential effects of prematurity on the long term, the inclusion of low‐volume centers, and the potential of FETO for severe iatrogenic complications. Therefore results may not be generalizable. The discussants concluded that although FETO may have its value it remains a procedure with a high risk for prematurity and it can be lethal when the balloon cannot be removed prior to delivery. Clinical trial registration: The TOTAL trials were registered at www.clinicaltrials.gov as NCT01240057 (severe) and NCT00763737 (moderate). Key points: What's already known about this topic? Congenital Diaphragmatic Hernia is a severe birth defect, with a 30% mortality in isolated cases. It can be diagnosed prior to birth and severity can be assessed by imaging. Fetal surgery has been proposed to increase survival chances. What does this study add? Two randomized clinical trials have investigated the effect of fetal surgery in severe and moderate hypoplasia. Survival was increased in severe cases, with increased prematurity. In moderate cases, effects were less. Discussants debate how these findings need to be implemented.